Penerapan Model Pembelajaran Project Work pada Mata Pelajaran Instalasi Tenaga Listrik - Pramono, Prasetyo; Candra, Oriza (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2024)
This research aims to apply the work project learning model to improve student activities and learning outcomes in the electrical power installation subject at SMK Negeri 1 Mandau. The method used in this research is a quantitative approach with an experimental research type, the experimental research design used is the Pre-Experimental Design method, One Group Pretest-Posttest design type. This design involves one group being given a pretest (O1), given treatment (X), and given a posttest (O2). The first measurement is carried out before the subject is given treatment and the second measurement is carried out after the subject is given treatment. Based on the results of research data, it was found that students' learning activities increased from before the treatment was given to treatment, while the increase in learning outcomes showed an increase in learning outcomes. These results can be seen from the knowledge domain, namely the pretest and posttest results which were analyzed using the N-Gain Score formula into the medium category. So it can be concluded from this research that implementing the Project Work learning model can increase the activity and learning outcomes of XI TITL 1 SMK Negeri 1 Mandau students.